1994
DOI: 10.1002/jemt.1070270406
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial matrix granules: Their behavior during changing metabolic situations and their relationship to contact sites between inner and outer mitochondrial membranes

Abstract: Since their discovery in the early fifties mitochondrial granules have been the subject of many researches. Some twenty years ago two hypotheses on their function were introduced. Peachey thought that the granules were a sink of cations and that they would eventually regulate the concentrations of these ions. Alternatively, Barnard thought that the granules were precursors of the mitochondrial inner membrane. There are only a few data on organic constituents of the granules. Phospholipids (e.g., cardiolipin) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…As much as it occurs in tissues from hibernating mammals (Romita and Gatti 1980;Malatesta et al 2002) and in quiescent cells in culture (Roeder et al 1989), residual bodies were found to accumulate in the cytoplasm during DADLE treatment and to disappear after recovery. Granules accumulated in the mitochondrial matrix under DADLE administration (these are thought to represent storage sites for inorganic and organic components, such as calcium, phosphorous, lipids, glycoproteins, citochrome c oxidase, which are needed for respiratory functions: Jacob et al 1994); matrix granules disappeared after removing the opioid from the culture medium, consistent with the observations made on different tissues of both hibernating and non-hibernating species, during quiescence and after strong metabolic activation (Jacob et al 1994;Malatesta et al 2001b).…”
Section: Discussionsupporting
confidence: 81%
“…As much as it occurs in tissues from hibernating mammals (Romita and Gatti 1980;Malatesta et al 2002) and in quiescent cells in culture (Roeder et al 1989), residual bodies were found to accumulate in the cytoplasm during DADLE treatment and to disappear after recovery. Granules accumulated in the mitochondrial matrix under DADLE administration (these are thought to represent storage sites for inorganic and organic components, such as calcium, phosphorous, lipids, glycoproteins, citochrome c oxidase, which are needed for respiratory functions: Jacob et al 1994); matrix granules disappeared after removing the opioid from the culture medium, consistent with the observations made on different tissues of both hibernating and non-hibernating species, during quiescence and after strong metabolic activation (Jacob et al 1994;Malatesta et al 2001b).…”
Section: Discussionsupporting
confidence: 81%
“…As for the Golgi complex, a decrease in size has been observed in pancreatic acinar cells under resting and starvation conditions, when a reduction of secretion occurs (Jamieson and Palade 1971;Bendayan et al 1985); however, under conditions of stimulated secretion, the Golgi complex increases in size . The electron-dense particles that are observed in the mitochondrial matrix during hibernation and that disappear upon arousal have been known since the fifties (Palade 1952;Sjostrand and Rhodin 1953) and have been observed in many cell types (see Jacob et al 1994) but their nature remains to be elucidated. Some authors have suggested that they contain calcium (Peachey 1964), whereas others have detected phospholipids (André and Marinozzi 1965;Barnard 1981) or glycoproteins (Bonucci et al 1973).…”
Section: Discussionmentioning
confidence: 96%
“…An increased presence of mitochondrial matrix granules, precipitates made of phospholipids, glycoprotein, and calcium-precipitable lipoprotein, was also observed in mitochondria from Txnip-KO compared with WT hearts (Figure 2, E and G). A previous report suggested that matrix granules serve to increase calcium concentration in the mitochondrial matrix, enhancing the activity of dehydrogenases to control energy metabolism (24). It is thus possible that decreased mitochondrial respiration might be partially compensated by these morphological adaptations in Txnip-KO mice.…”
Section: Figurementioning
confidence: 95%